Efeito da cantaxantina dietética para matrizes pesadas com idade avançada e do período de armazenamento dos ovos sobre a fertilidade, rendimento de incubação, nutrientes da gema e desenvolvimento embrionário - Julia Sampaio Rodrigues Rocha (2011)
Two experiments were conducted. In experiment I, were evaluated the effect of canthaxanthin (Carophyll Red ®) added to the broiler breeders diet and egg storage on egg quality, yolk nutrients, fertility, incubation yield and embryo development. In experiment II, were evaluated the effects of dietary canthaxanthin and aging on broiler breeder fertility. Eggs of two sheds of the same Cobb flock, age and lines, with similar fertility and hatchability monitored for five weeks before the start of the experiments. In experiment I, the treatments were defined by the diets (with and without 6ppm canthaxanthin added to broiler breeder diets) and periods of egg storage (three and seven days) in a completely randomized in a factorial design 2 x 2 (two diets x two periods of egg storage). In experiment II, the treatments were defined by the diets (with and without canthaxanthin added to broiler breeder diets) and broiler breeder ages (50, 51, 55, 59 and 60 weeks of age). The design was completely randomized design in 2 x 5 split plot arrangement (two diets x five ages). In experiment I, the addition of canthaxanthin to the diet increased concentrations of canthaxanthin and vitamin A and reduced the amount of vitamin E in egg yolk, improved fertility and hatchability and decreased embryonic mortality from 15 days of incubation. The egg storage for seven days reduced egg quality, promoted oxidation of yolk lipids and vitamins, delayed embryonic development, reduced hatchability and increased embryonic mortality after 15 days of incubation. In experiment II, it was observed that after 50 weeks of age, broiler breeder fertility continually reduced and the addition of canthaxanthin to the diet minimizes the negative impact aging on fertility. Canthaxanthin can be used as antioxidants in broiler breeders diets to minimize the negative effects of storage on the incubation yield and of aging on fertility.